PERANAN LABORATORIUM PENDIDIKAN UNTUK MENUNJANG PROSES PERKULIAHAN JURUSAN KEPERAWATAN GIGI POLTEKKES DENPASAR - Ni Luh Putu Kertiasih (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Laboratory education is an academic support unit at the college, which is used to carry out educational activities, research, and community service; using 1) the equipment and 2) materials, 3) based on certain scientific method. laboratory is defined as a place to hold a trial, investigation, and so related to physics, chemistry, and biology or other science fields. Broadly speaking laboratories in the educational process has the functions are as follows: 1). As a place to practice developing intellectual skills. 2). Develop motor skills. 3). Provide and cultivate the courage to seek the essence of scientific truth of the object in something of an environmental and social nature. Some role of laboratories in education, especially in the field of skills among students, among others: (1) To train students to be skilled in conducting the practice of engineering skills for the various sub-fields of skills, (2) Assemble and install the equipment / laboratory equipment engineering skills, (3) Creating and designing components specific-component in a wide range of expertise by using laboratory facilities engineering skills, (4) Serving students and the community in conducting educational practice through laboratory equipment engineering skills as a medium, and (5) Maintain and repair equipment / laboratory equipment engineering skills